Development of Motion Graphic Animation Video Learning Media Assisted by Animakers Based on Problem Based Learning (PBL) in Demak Kingdom Material - Reza Indah Lestari; Kasim Kasim; Meldawati Meldawati (PT. Anagata Sembagi Education, 2024)
This research is motivated by the fact that active learning activities are still relatively low and the lack of use of learning media that utilize technology, especially in History subjects. The formulation of the problem in this study is how to design media development and implementation of animated video learning media Motion Graphics assisted by Animaker based on Problem Based Learning (PBL) on the material of the Kingdom of Demak. The purpose of this study is to describe the design of learning media development and implementation of animated video learning media . This research uses the research and development method (Research and Development) with the ADDIE model which consists of 5 (five) stages, namely Analysis , Design , Development , Implementation. and Evaluation . The results of this study indicate that the developed animated video learning media meets the criteria of